2023
DOI: 10.3390/cancers15072055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pathological Outcome and Recurrence Rate between En Bloc Transurethral Resection of Bladder Tumor and Conventional Transurethral Resection: A Meta-Analysis

Abstract: Current treatment for non-muscle invasive bladder cancer (NMIBC) is the conventional transurethral resection of bladder tumor (CTURBT), but the en bloc transurethral resection of bladder tumor (ERBT) has been gaining more attraction in recent years considering better specimen integrity. Thus, we conducted this meta-analysis to compare the safety and efficacy of ERBT versus CTURBT. Trials were collected from an online database. The primary outcomes included identification of detrusor muscle in specimen, residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…When compared to cTURBT, ERBT has shown a notable association with reduced rates of bladder perforation and ONR, suggesting that it may offer a safer surgical alternative for NMIBC patients. 16,[18][19][20][21][22] The pooled ORT result reported by Teoh et al 16 exhibited disparities from the findings of other five meta-analyses. [18][19][20][21][22] In our metaanalysis, comprised of five studies, ERBT and cTURBT required a similar amount of time to complete the surgery.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…When compared to cTURBT, ERBT has shown a notable association with reduced rates of bladder perforation and ONR, suggesting that it may offer a safer surgical alternative for NMIBC patients. 16,[18][19][20][21][22] The pooled ORT result reported by Teoh et al 16 exhibited disparities from the findings of other five meta-analyses. [18][19][20][21][22] In our metaanalysis, comprised of five studies, ERBT and cTURBT required a similar amount of time to complete the surgery.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, these problems are discussed in several studies (including meta-analysis and RCT). 17,22,31 Using a combination of umbrella review and meta-analysis, we demonstrated that ERBT had a better or comparable perioperative outcome than cTURBT. Furthermore, NMIBC patients undergoing ERBT exhibited improved 3 and 12 month RFS compared to those receiving cTURBT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the standard TURBT is thought to have some problems, such as the fact that it removes tumor cells partially and doesn't include the detrusor muscle in the specimen. This removal method doesn't follow the basic rules of oncological surgery, which means it can't effectively find and treat bladder cancer (Kim & Patel, 2020a;Wang et al, 2023). In the past few years, improvements in medical tools like surgical techniques and instruments, as well as micro or small tumor imaging, have made it possible for more than one way to be used instead of conventional TURBT (Kramer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En bloc resection of bladder tumor (ERBT) has emerged as a promising alternative. This technique offers several potential advantages, such as the ability to resect the tumor and its base as a single piece and improved specimen collection for accurate pathological assessment with increased DM sampling [6,7]. Additionally, ERBT may lead to reduced perioperative complications, a decreased risk of tumor shedding and implantation, and potentially lower recurrence rates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%